2020
DOI: 10.2174/1381612826666191230142638
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenesis Potential of Phytochemicals for the Therapeutic Management of Tumors

Abstract: The role of angiogeneses during the growth and progression of tumors is well documented. Likewise, a balance is generally maintained between the cellular proliferation and the apoptosis, therefore, the tumors can persist for years in a dormant phase. During the past few years, many hypotheses have been proposed relating to the importance of tumor angiogenesis for the development and spread of tumors and preventive or therapeutic capacity of angiogenesis inhibitors as a potential target for controlling the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Anti-angiogenic molecules such as VEGFR1, thrombospondins, and semaphorins could antagonize pro-angiogenic molecules such as VEGF and Ang2. The current anti-angiogenic drugs such as bevacizumab, sunitinib, sorafenib, aflibercept, axitinib, pazopanib, and regorafenib are applied to the treatment of tumor patients [30,[108][109][110]. However, antiangiogenic drugs cannot effectively stop the neovascularization process because hypoxia promotes the formation of VM, and the formation of VM could reduce the therapeutic effect.…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…Anti-angiogenic molecules such as VEGFR1, thrombospondins, and semaphorins could antagonize pro-angiogenic molecules such as VEGF and Ang2. The current anti-angiogenic drugs such as bevacizumab, sunitinib, sorafenib, aflibercept, axitinib, pazopanib, and regorafenib are applied to the treatment of tumor patients [30,[108][109][110]. However, antiangiogenic drugs cannot effectively stop the neovascularization process because hypoxia promotes the formation of VM, and the formation of VM could reduce the therapeutic effect.…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…were screened for cancer prevention and adjuvant therapy [7,44,58]. There are many consistencies on tumor types and progression between bet animals and human.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the growth and progression of cancerous tumours beyond a certain size require pathogenic angiogenesis, and therefore angiogenesis inhibition can prove to be an effective strategy in cancer management [246,247]. Typically, the focus on cancer management by angiogenesis inhibition in the recent past has been to develop inhibitors against its stimulant molecules like VEGFR-2, protease inhibitors, etc.…”
Section: Expert Opinion On the Recent Perspectives On Cancer Managementmentioning
confidence: 99%